2011
DOI: 10.1111/j.1365-2826.2011.02177.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Hypothalamic Kiss1 Expression during Activation of the Pulsatile Release of Luteinising Hormone in Maturing Ewe Lambs

Abstract: Onset of puberty is characterised by a marked increase in the frequency of release of gonadotrophin-releasing hormone (GnRH) and luteinising hormone (LH). The Kiss1 gene plays a critical role in pubertal development, and its product, kisspeptin, stimulates GnRH and LH release. In the present study, we tested the hypothesis that Kiss1 gene expression in the preoptic area (POA) and hypothalamus increases during maturation of the reproductive neuroendocrine axis in association with increased LH pulsatility. Ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 43 publications
6
54
3
3
Order By: Relevance
“…In contrast, in 6-month-old prepubertal female lambs, only single and very lightly stained kp perikarya have been observed in this hypothalamic area (Nestor et al, 2012), similarly to the observations in peripubertal lambs in our study. High expression of kp mRNA has also been observed, however (Redmond et al, 2011). These data suggest that during prepubertal development of lambs, the post-translational processing of kp does not occur in the kp perikarya distributed in the MPOA-AHA.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In contrast, in 6-month-old prepubertal female lambs, only single and very lightly stained kp perikarya have been observed in this hypothalamic area (Nestor et al, 2012), similarly to the observations in peripubertal lambs in our study. High expression of kp mRNA has also been observed, however (Redmond et al, 2011). These data suggest that during prepubertal development of lambs, the post-translational processing of kp does not occur in the kp perikarya distributed in the MPOA-AHA.…”
Section: Discussionmentioning
confidence: 85%
“…Recent data obtained on prepubertal (5-to 6-month-old) and post pubertal (9-month-old) female lambs also showed a predominant population of kp perikarya in the ARC nucleus that increased with age (Nestor et al, 2012). The expression of Kiss1 mRNA is also activated in the ARC nucleus of ewe lambs during juvenile development from 25-35 weeks of age (Redmond et al, 2011). It was demonstrated on ovariectomized ewes treated acutely with E2 that the number of kp arcuate cells co-labelled with c-fos increased 6-fold, so the authors conclude that these kp neurons are involved in generating the positive feedback preovulatory GnRH/LH surge (Smith et al, 2009b).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, expression of KiSS-1 in the ARC and the rostral preoptic area are differentially regulated by gonadal steroids (Estrada et al, 2006;Smith et al, 2005Smith et al, , 2007Tomikawa et al, 2010). It has recently been shown that increased LH pulsatility during sexual maturation in the ewe is associated with a reduction in the suppressive effects of estradiol on KiSS-1 expression (Redmond et al, 2011). The fundamental importance of kisspeptin in the onset of puberty raises the question as to whether kisspeptin has a central role in the timing of pubertal events associated with metabolic state or body energy reserves.…”
Section: Kisspeptin Regulates Gonadotropin Secretion and Pubertal Devmentioning
confidence: 99%
“…The hypothalamic ARC contains neurons that are involved in regulating pubertal onset and maintenance of estrous cycles through the control of gonadotropin secretion Redmond et al, 2011). High-throughput RNA sequencing reads were obtained from the ARC from gilts representing pre-and postpubertal time points and early and late pubertal gilts fed 3 different dietary treatments.…”
Section: Ribonucleic Acid Sequencing Of Arcuate Nucleus Provides Exprmentioning
confidence: 99%